1995
DOI: 10.1002/aja.1002030402
|View full text |Cite
|
Sign up to set email alerts
|

Mouse half embryos: Viability and allocation of cells in the blastocyst

Abstract: We have investigated the developmental capacity of mouse embryos in which one blastomere was destroyed by lysis at the 2-cell stage. The allocation of cells to the trophectoderm and inner cell mass (ICM) was documented by differential cell counts on single embryos after 2 days under different culture conditions. Viability and further developmental potential were tested by embryo transfer to foster mothers. The conditions used were: (1) in vitro culture in modified BMOC-2 medium, (2) in vivo oviduct transfer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…Where a major imbalance did occur, it may have been due to damage to one of the blastomeres during the process of separation. Very similar rates of development were also observed in experiments in which one blastomere of a two-cell embryo was damaged to prevent it from dividing, while the other was allowed to progress in its development (Tables 3), albeit within the confines of the original ZP, again confirming data reported by others [39,50,51]. Together, these experiments support the notion that the zygotic clock, that is, the time after fertilization, rather than number of cells in the embryo determines when differentiation begins and are consistent with the notion that blastomeres from two-cell stage embryos are developmentally equivalent in their potential.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Where a major imbalance did occur, it may have been due to damage to one of the blastomeres during the process of separation. Very similar rates of development were also observed in experiments in which one blastomere of a two-cell embryo was damaged to prevent it from dividing, while the other was allowed to progress in its development (Tables 3), albeit within the confines of the original ZP, again confirming data reported by others [39,50,51]. Together, these experiments support the notion that the zygotic clock, that is, the time after fertilization, rather than number of cells in the embryo determines when differentiation begins and are consistent with the notion that blastomeres from two-cell stage embryos are developmentally equivalent in their potential.…”
Section: Discussionsupporting
confidence: 88%
“…We suspect, for example, that the two expanded blastocysts shown in Figure 6B, each of which had over 30 cells, would have a poor chance of providing fetuses in view of the few ICM cells present in either embryo. It is well established that blastocysts with a small ICM rarely, if ever, develop to form fetuses [50]. By contrast, demiembryos generated after damaging one member of a sister pair at the two-cell stage, although possessing similar numbers of cells as the zona-free demiembryos, provided a more balanced ratio of ICM to TE cells in their blastocysts (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…However, the stem cell pool for fetal and extraembryonic lineages is limited and, if depleted, may influence the pattern of later development. Past experimental studies using mostly the mouse have demonstrated some resilience and regulative capacity within embryos to reductions in cell numbers mediated by different manipulative procedures such as cell ablation, embryo bisection, or by mitomycin treatment to deplete the ICM [127][128][129][130][131][132]. These studies have revealed that, during postimplantation development, from about Day 12 or later, proliferative control mechanisms may compensate for early depletion of cells and result in reasonable rates of fetal survival.…”
Section: Embryo Proliferation and Future Potentialmentioning
confidence: 98%
“…These studies have revealed that, during postimplantation development, from about Day 12 or later, proliferative control mechanisms may compensate for early depletion of cells and result in reasonable rates of fetal survival. Nevertheless, artificial reduction in embryo cell numbers may significantly decrease the proportion of ICM derivatives [128], reduce the rate of primitive endoderm formation and the size of egg cylinder stage conceptuses up to Day 8 after transfer, delay the timing of gastrulation, retard morphogenesis, and significantly increase the rate of pregnancy loss [127,[129][130][131][132]. However, during postnatal development, mice derived from half embryos grow at similar rates to controls [133].…”
Section: Embryo Proliferation and Future Potentialmentioning
confidence: 99%
“…they do not test the potency of individual blastomeres. Killing or removing one blastomere at the 2-cell stage produces blastocysts and mice, suggesting that the embryo can compensate for the loss of one blastomere (Tarkowski, 1959;Papaioannou et al, 1989;Papaioannou and Ebert, 1995). However, although yields can be very high, like the morulae bisections these experiments do not test the potential of both blastomeres, which is the crucial element of the Driesch test and the only way to rule out an early determination event.…”
mentioning
confidence: 99%